Boosting Li-Ion Battery Pack Lifespan with Active On-Load Balancing - Salam S. Hussein; Ahmed J. Abid; Adel A. Obed; Ameer L. Saleh; Reheel J. Hassoon (Journal of Techniques)
Due to the repeated cycles of charging and discharging, battery manufacturers cannot ensure perfect cell balance. Cell balancing is considered essential for equalizing each battery cell to the same state of charge level in a series configuration. Lithium-ion (Li-ion) batteries can be damaged or have their lifespan decreased by improper discharge processes. This study investigates battery balance during discharge by analyzing the state of charge (SoC) and current distribution of a 3-cell battery pack based on a multi-transformer shared flyback converter (F-C) under varying load conditions. A balanced approach is employed to control individual cells using a dedicated switch for each cell during the discharge process. The results indicate that the proposed active balancing method can enhance the Li-ion pack's balancing capacity while reducing the disparity in residual energy among the battery cells. The unique contribution of this research lies in the active balancing approach, which offers efficient and effective battery management during discharge. This approach provides crucial insights for the future development of improved battery systems. Therefore, Given the linearly decreasing target SoC, the average error over all time points is approximately 4.29%.